Two new species of Metapocyrtus (Metapocyrtus) Heller 1912 from Mindanao, Philippines (Curculionidae, Entiminae, Pachyrhynchini) - Bollino, Maurizio; Bordoni, Arnaldo (Zootaxa, 2021)
Two new species of Curculionidae, Pachyrhynchini, Metapocyrtus waoensis sp. nov., and M. lanaoensis sp. nov., both from western Mindanao are described. Images of habitus and fully everted endophallus and illustrations of male genitalia are provided for each species.